2016
DOI: 10.1080/14767058.2016.1214699
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cognitive-behavioral stress management on psychological stress and glycemic control in gestational diabetes: a randomized controlled trial

Abstract: Cognitive-behavioral stress management reduces stress in women with gestational diabetes and reducing stress may also improve the pregnancy outcomes, especially whose glycemic along with stress is not adequately controlled by medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 18 publications
2
35
0
2
Order By: Relevance
“…Twenty‐eight RCTs reported results of 1944 pregnant women. Nine RCTs were conducted in West Asia (Iran (Asghari et al., 2016; Bastani et al., 2005; Khorsandi et al., 2016; Mohammad & Shima, 2019; Nasiri et al., 2018; Shahtaheri et al., 2016; Zaheri et al., 2017) and Turkey (Ertekin et al., 2018; Fiskin & Sahin, 2018)); seven in Europe (Greece (Kantziari et al., 2019; Tragea et al., 2014), Germany (Richter et al., 2012), Ireland (Matvienko‐Sikar & Dockray, 2017), Sweden (Lönnberg et al., 2020; Scherer et al., 2016) and UK (Krusche et al., 2018)); five in USA (Guardino et al., 2014; Jallo et al., 2014; Urizar et al., 2019; Vieten & Astin, 2008; Zhang & Emory, 2015); three in India (Deshpande et al., 2013; Muthukrishnan et al., 2016; Satyapriya et al., 2009); two in China (Pan et al., 2018; Zhang et al., 2019); and two in Australia (Beattie et al., 2017; Woolhouse et al., 2014). The mean age of the participants ranged from 18 to 35 years old.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐eight RCTs reported results of 1944 pregnant women. Nine RCTs were conducted in West Asia (Iran (Asghari et al., 2016; Bastani et al., 2005; Khorsandi et al., 2016; Mohammad & Shima, 2019; Nasiri et al., 2018; Shahtaheri et al., 2016; Zaheri et al., 2017) and Turkey (Ertekin et al., 2018; Fiskin & Sahin, 2018)); seven in Europe (Greece (Kantziari et al., 2019; Tragea et al., 2014), Germany (Richter et al., 2012), Ireland (Matvienko‐Sikar & Dockray, 2017), Sweden (Lönnberg et al., 2020; Scherer et al., 2016) and UK (Krusche et al., 2018)); five in USA (Guardino et al., 2014; Jallo et al., 2014; Urizar et al., 2019; Vieten & Astin, 2008; Zhang & Emory, 2015); three in India (Deshpande et al., 2013; Muthukrishnan et al., 2016; Satyapriya et al., 2009); two in China (Pan et al., 2018; Zhang et al., 2019); and two in Australia (Beattie et al., 2017; Woolhouse et al., 2014). The mean age of the participants ranged from 18 to 35 years old.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 14 articles selected for the evaluation of the psychosocial intervention program, studies conducted prior to 2013 could not be identified. Eight studies (57.1%) [23][24][25][26][27][28][29][30] were published before 2018, and six studies (42.9%) [31][32][33][34][35][36] were published after 2018. In the past 3 years, psychosocial support interventions for women with GDM have been actively studied, and it can be confirmed that various intervention methods such as smartphone-or web-based interventions are being used.…”
Section: General Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…In the past 3 years, psychosocial support interventions for women with GDM have been actively studied, and it can be confirmed that various intervention methods such as smartphone-or web-based interventions are being used. There were nine international studies and five domestic studies done in Korea (n = 5, 35.7%) [28][29][30]34,36], which was the country with the most studies included in this analysis, followed by Iran (n = 4, 28.6%) [24,25,33,35], while one study (7.1%) each was included from Turkey [31], Netherlands [32], United Kingdom [23], Australia [26], and Ireland [27]. The total number of study participants was 1,331, with eight studies (57.1%) [24,25,28,[30][31][32][33]36] having more than 50 but fewer than 100 participants, three studies (21.4%) [23,26,35] having more than 100 participants, and three studies (21.4%) [27,29,34] having fewer than 50 participants.…”
Section: General Characteristics Of the Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…De acuerdo con la información de la tabla 7, existe evidencia de que las intervenciones psicológicas con base en la TCC tienen influencia favorable en el manejo de la enfermedad, en la reducción de sintomatología relacionada al estrés y otras problemáticas psicológicas. Se establece que la TCC es efectiva generando cambios estadísticamente significativos (Winkley et al, 2020), además proporciona una reducción estadísticamente significativa de los puntajes de estrés de dos semanas después (Zaheri et al, 2016). Por su parte, la intervención en línea obtiene resultados favorables, las intervenciones psicoeducativas demostraron que había mejora en niveles de glucosa, reducción de peso y circunferencia (mejorando hasta seis meses).…”
Section: Autoresunclassified